Bacillus circulans a Promising Biocontrol Agent of Locastra muscosalis a Defoliating Pest - Sharma, Ajay; Verma, T. D.; Shirkot, C. K. (Indian Forester, 2006)
Locastra muscosalis is a serious defoliating pest of Pistacia intergerrima, apple, poplars and walnut. Its larvae feed gregariously on the foliage. The larvae were found to die from 3rd instar onwards. Bacillus circulans was found to be the cause of mortality. The bacterial was isolated and was tested for its pathogenecity at different O.D. levels at 540 nm. The 4th instar was found to be most susceptible to the bacteria in all levels.